Liposomes with asymmetric bilayers produced from inverse emulsions for nucleic acid delivery. (3rd July 2019) - de Matos, Maria B. C.; Miranda, Bárbara S.; Rizky Nuari, Yudha; Storm, Gert; Leneweit, Gero; Schiffelers, Raymond M.; Kok, Robbert J.
Abstract: Asymmetrical lipid nanoparticles are interesting nanocarriers for charged molecules, like nucleic acids. They promise control over inner and outer charge. High charge density on the inside is favourable for efficient condensation and charge neutralisation of highly charged biopharmaceuticals, while a neutral or slightly negative outer layer promotes biocompatibility. The main goal of this work was the development and characterisation of asymmetric liposomes, prepared using water-in-oil (w/o) nanoemulsions of phospholipids (PLs) and squalene in a centrifugal field. This method enables the control over the lipid composition of each monolayer. Liposomes were prepared by passing PL w/o nanoemulsions through an oil–water interface previously saturated with PLs. We used N-(7-Nitrobenz-2-Oxa-1, 3-Diazol-4-yl)-1, 2-Dihexadecanoyl-sn-Glycero-3-Phosphoethanolamine (NBD-PE) or N-(7-Nitrobenz-2-Oxa-1, 3-Diazol-4-yl)-1, 2-Dihexadecanoyl-sn-Glycero-3- phosphocholine (NBD-PC) as a fluorescent marker for either the inner or outer lipid layer and plasmid DNA (pDNA) as nucleic acid payload. The final liposomes had sizes below 200 nm and polydispersity indexes of 0.3 and had a bilayer asymmetry of 70%, thus shielding the charge of positive PLs in the inner bilayer leaflet. Final formulations were examined using negative staining transmission electron microscopy (TEM). Plasmid encapsulation efficiency of the method was 10–15%. Our results indicate that the w/o nanoemulsion-centrifugation method allows the successful production of liposomes with tailored features for encapsulation of nucleic acid therapeutics.